Is There an Effect of Fetal Mesenchymal Stem Cells in the Mother–Fetus Dyad in COVID-19 Pregnancies and Vertical Transmission? - Samara, Athina; Herlenius, Eric (Frontiers in Physiology, 2021)
Due to the polysystemic nature of COVID-19, during the present pandemic there have been serious concerns regarding pregnancy, vertical transmission and intrapartum risk. The majority of pregnant patients with COVID-19 infection presents with mild or asymptomatic course of the disease. Some cases were hospitalized and few needed intensive care unit (ICU) admission, or mechanical ventilation. There have also been scarce case reports where neonates required mechanical ventilation post COVID-19 pregnancies. Without approved therapies other than dexamethasone, advanced mesenchymal cell therapy is one immunomodulatory therapeutic approach that is currently explored and might hold great promise. We suggest that the circulating fetal stem cells might have an immune-protective effect to mothers and contribute to the often mild and even asymptomatic COVID-19 pregnancies. Thus, COVID-19 pregnancies come forth as a paradigm to be further and more comprehensively approached, to understand both the mechanism and action of circulating stem cells in immunoprotection and hypoxia in microcirculation.